PENERAPAN APLIKASI LET'S READ UNTUK MENINGKATKAN KEMAMPUAN LITERASI DIGITAL SISWA SEKOLAH DASAR - Tiara Suci Andini; Apriyanti Widiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The growing demands of the digital era call for early mastery of digital literacy among students, including at the elementary level. Despite this need, many young learners still struggle to engage with technology for meaningful literacy activities. This article examines the integration of the Let’s Read digital reading application in supporting digital literacy development among sixth-grade students at SDN Sukamantri 01 Tambelang. Employing a qualitative descriptive approach with a case study design, data were collected from six students and one classroom teacher through observation, in-depth interviews, and documentation. Data analysis followed Miles and Huberman’s interactive model. The results indicate that the use of Let’s Read contributes positively to students' digital literacy, particularly in reading comprehension, independent information-seeking, and reading motivation. Key enabling factors include access to devices, school-level support, and the app’s user-friendly features. Conversely, implementation is hindered by limited digital competence among teachers, unstable internet connections, and the lack of digital material integration into lessons. The study recommends structured digital literacy training for educators and improved school infrastructure to enhance the sustainability of digital-based learning.